2015
DOI: 10.1194/jlr.d059824
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin fingerprinting of leukocytes by MALDI-TOF/MS as a screening tool for Barth syndrome

Abstract: mitochondrial respiratory chain dysfunction ( 1-4 ). It results from loss-of-function mutations of the tafazzin ( TAZ ) gene ( 5 ).The major consequence of this loss-of-function is the defi cient remodeling of the mitochondrial phospholipid cardiolipin (CL), a process that normally leads to the mature acyl composition ( 6, 7 ). CL is the signature lipid of mitochondria, where it is an important constituent of the inner membrane, essential for supercomplex formation, oxidative phosphorylation (i.e., mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…In fatty liver disease, TAZ downregulation promotes lipid accumulation and suppresses mitochondrial respiratory function 57. Moreover, TAZ is also involved in mitophagy regulation,58 mitochondrial cardiolipin metabolism,59 and the mitochondrial redox balance 60. In the present study, we found that TAZ deletion evoked mitochondrial bioenergetics disorder, mitochondrial oxidative injury, mitochondrial potential reduction, mitochondrial fission, and mitochondrial apoptosis.…”
Section: Discussionsupporting
confidence: 60%
“…In fatty liver disease, TAZ downregulation promotes lipid accumulation and suppresses mitochondrial respiratory function 57. Moreover, TAZ is also involved in mitophagy regulation,58 mitochondrial cardiolipin metabolism,59 and the mitochondrial redox balance 60. In the present study, we found that TAZ deletion evoked mitochondrial bioenergetics disorder, mitochondrial oxidative injury, mitochondrial potential reduction, mitochondrial fission, and mitochondrial apoptosis.…”
Section: Discussionsupporting
confidence: 60%
“…Recently MALDI‐TOF/MS analysis has been successfully used to directly acquire lipid profiles of biological samples (Angelini, Babudri, Lobasso, & Corcelli, ; Angelini et al, , ; Angelini, Vortmeier, Corcelli, & Fuchs, ; Vitale et al, ). One of the advantages of this analytical approach is that minute amounts of cell membranes are required for lipid analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Three microliter of lipid samples in chloroform solution were diluted in 27 μl of 2-propanol/acetonitrile (60/40, by volume), then 10 μl of the diluted solution were mixed with 10 μl of matrix solution (9-AA, 10 mg/ml in 2-propanol/acetonitrile 60/40, by volume), as previously described (Sun et al, 2008; Angelini et al, 2015). At variance, spectra of neutral lipids were acquired by preparing the same matrix solution in the presence of sodium acetate, as previously described (Sun et al, 2008).…”
Section: Methodsmentioning
confidence: 99%